Nasal Variability at the Contact Frontier: An Autosegmental-Moraic Analysis of Papuan Malay - Denny Irjanto Siagian (Austronesian: Journal of Language Science & Literature, 2026)
Researchers have recently started paying more attention to Papuan Malay (PM) because the language is widely used by people from different ethnic and linguistic backgrounds in Papua and beyond. Despite the growing number of studies on PM, in-depth phonological analyses remain limited. Previous studies have mainly discussed PM phonology descriptively, while analyses of nasal fluctuation from a moraic and autosegmental perspective remain limited. Using a qualitative contact-phonological approach, this study analyzes spontaneous PM speech collected through natural conversations, semi-structured interviews, and targeted elicitation from thirty-eight multilingual speakers in Manokwari, representing diverse first-language backgrounds across Papua. This article focuses on the conditioned fluctuation between the alveolar nasal [n] and the velar nasal [ŋ] in spoken discourse. The study analyzes this fluctuation using autosegmental moraic phonology to examine its underlying structure. The findings indicate that the alternation between [n] and [ŋ] is not arbitrary, but is mainly influenced by phonological assimilation. The analysis shows that sound changes occur more frequently in environments where nearby sounds influence one another. This study demonstrates that nasal fluctuation in PM is conditioned by prosodic and assimilatory environments rather than free variation alone. The findings suggest that variation in PM is not entirely unpredictable but follows systematic phonological patterns shaped by multilingual interaction and pronunciation habits. By integrating autosegmental, moraic, and contact phonological frameworks, this study advances a unified account of nasal variability in PM that treats phonetic variation not as noise, but as structured evidence of how multilingual systems negotiate phonological identity at the coda boundary.